Organoruthenium (II) complexes featuring pyrazole-linked thiosemicarbazone ligands: synthesis, DNA/BSA interactions, molecular docking, and cytotoxicity studies - Khanvilkar, Priyanka; Dash, Soumya R.; Banerjee, Devjani; Vohra, Aliasgar; Devkar, Ranjitsinh; Chakraborty, Debjani (Applied Organometallic Chemistry, 2021)
A series of pyrazol-derived thiosemicarbazone ligands (L1-L4) were synthesized and reacted with [Ru(p-cymene)(mu-Cl)Cl](2) to yield a series of ``piano-stool''-type binuclear ruthenium (II)-arene-thiosemicarbazone complexes (C1-C8) of the general type [(Ru(eta(6)-p-cym)L)(2)(mu-im/azpy)] Cl1-2 (L = diphenylpyrazole thiosemicarbazone; cym = p-cymene; im = imidazole; azpy = 4,4 `-azopyridine). The thiosemicarbazone ligands act as N and S donors binding to the Ru(II) center via the imine nitrogen and the thione sulfur atoms. The complexes were characterized by NMR, FTIR, UV-Vis spectroscopy, and ESI+ mass spectrometry. The binding of the complexes to calf thymus deoxyribonucleic acid (CT-DNA) and bovine serum albumin (BSA) was evaluated, and it has been established that the binuclear complexes have good binding efficacies with DNA (K-b = 10(4)-10(5) M-1) and BSA (K-a = 10(5)-10(6) M-1). This is attributed to the arene moieties present in the ligands of the complexes that can have hydrophobic interactions with DNA/BSA. Ethidium bromide (EB) displacement studies and DNA viscosity measurements revealed intercalative interaction of the complexes with DNA. Static interaction of the complexes with BSA was revealed by fluorescence quenching studies. Molecular docking studies confirmed base stacking, H-bonding, and hydrophobic interactions with the biomolecules. In vitro antiproliferative studies of the complexes affirmed that the complexes are cytotoxic towards the HeLa (human cervical cancer) cell line with IC50 values in range of 17.3-41.3 mu M.
Keywords: Binuclear ruthenium (II) complexes; BSA binding interactions; DNA; HeLa human cervical carcinoma; pyrazole-derived thiosemicarbazone